VD_FINDINFO Décision / 2013 / 122 vom 4. Dezember 2012 - VD Tribunal cantonal (2012)
FRAIS DE LA PROCÉDURE, FAUTE, NON-LIEU | 319 al. 1 CPP (CH), 393 al. 1 let. a CPP (CH), 426 al. 1 CPP (CH), 426 al. 2 CPP (CH)